An Overview of the Clinical Use of Antimuscarinics in the Treatment of Overactive Bladder - Anastasios Athanasopoulos; Konstantinos Giannitsas (Advances in Urology)
Overactive bladder is a common and bothersome condition. Antimuscarinic agents, as a class, are the cornerstone of medical treatment of overactive bladder. They offer significant improvements in symptoms and patients’ quality of life. Antimuscarinics are generally well tolerated with mild and predictable side effects. Available antimuscarinics have small, yet statistically significant, differences in their efficacy and tolerability profiles. In clinical practice, finding the agent that offers the optimum balance of efficacy and side effects for an individual patient remains the major challenge.